Evidence-Based Surgical Treatments for Chronic Pancreatitis - Kleeff, Joerg; Stoess, Christian; Mayerle, Julia; Stecher, Lynne; Maak, Matthias; Simon, Peter; Nitsche, Ulrich; Friess, Helmut (Deutsches Ärzteblatt international, 2016)
If conservative treatment of chronic pancreatitis is unsuccessful, surgery is an option. The choice of the most suitable surgical method can be difficult, as the indications, advantages, and disadvantages of the available methods have not yet been fully documented with scientific evidence.In April 2015, we carried out a temporally unlimited systematic search for publications on surgery for chronic pancreatitis. The target parameters were morbidity, mortality, pain, endocrine and exocrine insuffi - ciency, weight gain, quality of life, length of hospital stay, and duration of urgery. Differences between surgical methods were studied with network meta-analysis, and duodenum-preserving operations were compared with partial duodenopancreatectomy with standard meta-analysis.Among the 326 articles initially identified, 8 randomized controlled trials on a total of 423 patients were included in the meta-analysis. The trials were markedly heterogeneous in some respects. There was no significant difference among surgical methods with respect to perioperative morbidity, pain, endocrine and exocrine insufficiency, or quality of life. Duodenumpreserving procedures, compared to duodenopancreatectomy, were associated with a long-term weight gain that was 3 kg higher (p <0.001; three trials), a mean length of hospital stay that was 3 days shorter (p = 0.009; six trials), and a duration of surgery that was 2 hours shorter (p <0.001; five trials).Duodenum-preserving surgery for chronic pancreatitis is superior to partial duodenopancreatectomy in multiple respects. Only limited recommendations can be given, however, on the basis of present data. The question of the best surgical method for the individual patient, in view of the clinical manifestations, anatomy, and diagnostic criteria, remains open.
EVALuna2:15260